ANALISIS TAMBAHAN MANFAAT PENERAPAN ALAT MESIN PERTANIAN PADA USAHATANI PADI (Oryza sativa L) DI LAHAN PASANG SURUT KECAMATAN KURAU KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Zuraida (Fakultas Pertanian UVAYA Banjarmasin, 2022)
There were two groups observed in the rice farming activities in tidal rice fields type B with the Ciherang variety in Kurau District, Tanah Laut Regency, namely the approach to the group using agricultural machinery (Alsintan) and the group not using Alsintan. This study aims to compare the level of efficiency and additional benefits obtained by farmers in rice farming due to the application of technological innovations in agricultural machinery, both technically and financially, covering production costs, productivity, revenues and profits. This research was carried out in the planting season of 2021. The results of the research were that the agricultural group using Alsintan was technically more efficient with a higher productivity level of 4,126.76 kg/ha than the group that did not use Alsintan with a productivity level of 3,641.03 kg/ha. Financially obtained by farmers using Alsintan, namely the decreasing costs in farming to produce dry milled grain from Rp. 7,845,372.62/ha to Rp. 7,489,115,10/ha which is also evidenced by the increased efficiency level of RCR 2.29 for the non-user group. Alsintan becomes RCR 2.75 for the Alsintan user group. This shows the development of innovation in applying technology in utilizing agricultural machinery owned by their farmer groups to be used properly because here it can save time and labor costs to be more effective and efficient at Rp. 774,909.9/ha. Meanwhile, the additional economic benefits obtained by farmers are proven by the increase in the value of the Marginal Benefit Cost Ratio (MBCR) of 3.75, which means that by decreasing the cost of rice farming to produce milled dry unhulled rice by Rp. 100, the profit will be 3.75 times